The Evolution of Artificial Intelligence: A Theoretical Review of its Impact on Teaching and Learning in the Digital Age - Emerson Abraham Jackson (ZBW – Leibniz Information Centre for Economics, 2024)
This theoretical review explores the evolution of artificial intelligence (AI) and its impact on teaching and learning in the digital age. Investigating AI's integration into educational settings, the paper synthesises theoretical frameworks, empirical studies, and emerging trends. Drawing on constructivist, socio-cultural, and cognitive learning theories, the review analyses AI's implications for educational practices. It traces the historical development of AI in education, highlighting key milestones and the evolution of AI technologies. The paper adopts a theoretical framework to comprehensively analyse AI's impact, focusing on intelligent tutoring systems, adaptive learning platforms, virtual reality, natural language processing, and gamification. Theoretical foundations underscore AI's role in active learning, personalised environments, social interaction, and cognitive load management. The review addresses challenges, including equity, ethical considerations, and the evolving role of educators. It emphasises the need for clear ethical guidelines, professional development for educators, and ongoing research to navigate the evolving landscape of AI in education. Theoretical implications suggest a nuanced synthesis of technology and pedagogy, acknowledging the dynamic interplay between the two, and call for continued research to address technical challenges, ethical considerations, and effective strategies for professional development in this dynamic intersection of technology and education. – – Cette revue théorique explore l'évolution de l'intelligence artificielle (IA) et son impact sur l'enseignement et l'apprentissage à l'ère numérique. En examinant l'intégration de l'IA dans les environnements éducatifs, l'article synthétise des cadres théoriques, des études empiriques et des tendances émergentes. S'appuyant sur les théories constructivistes, socio-culturelles et d'apprentissage cognitif, la revue analyse les implications de l'IA pour les pratiques éducatives. Elle retrace le développement historique de l'IA dans l'éducation, mettant en évidence des jalons clés et l'évolution des technologies d'IA. L'article adopte un cadre théorique pour analyser de manière exhaustive l'impact de l'IA, en se concentrant sur les systèmes de tutorat intelligents, les plateformes d'apprentissage adaptatif, la réalité virtuelle, le traitement du langage naturel et la ludification. Les fondements théoriques soulignent le rôle de l'IA dans l'apprentissage actif, les environnements personnalisés, l'interaction sociale et la gestion de la charge cognitive. La revue aborde des défis tels que l'équité, les considérations éthiques et le rôle en évolution des éducateurs. Elle souligne la nécessité de lignes directrices éthiques claires, de développement professionnel pour les éducateurs et de recherches continues pour naviguer dans le paysage en évolution de l'IA dans l'éducation. Les implications théoriques suggèrent une synthèse nuancée de la technologie et de la pédagogie, reconnaissant l'interaction dynamique entre les deux, et appellent à des recherches continues pour relever les défis techniques, les considérations éthiques et les stratégies efficaces de développement professionnel dans cette intersection dynamique de la technologie et de l'éducation.
Keywords: A22; I21; O33; 330; Artificial Intelligence; Theoretical Review; Teaching and Learning; Digital Age